Glucocorticosteroid in Treatment of Severe Pneumonia - Felinda Ariani; Kaixiong Liu; Zhang Jing; Jieming Qu (Mediators of Inflammation)
Airway diseases such as pneumonia constitute a major health burden on a global scale; untreated pneumonia may develop to severe pneumonia and consequently lead to to fatal episodes of mortality and morbidity. The balance between inflammatory mediators is key for the outcome of the pulmonary infection; elimination of invading pathogen was marked by the release of cytokines and other inflammatory mediators from alveolar macrophages and glucocorticoid steroids (GCs) acting on the inflammatory component. Treatments of severe pneumonia with GCs have been developing for years with inconclusive results. In many cases GCs have been administered empirically without clinical evidence. Recent studies assess beneficial impact on treatment of severe pneumonia by suggesting specific dosage, period of administration, and tapered dosage.